A kind of acid and alkali resistant geotextile and preparation method thereof

By forming a modified glue layer and a spray-coated modified layer on the geotextile, the problem of insufficient strength and acid and alkali resistance stability of the geotextile is solved, and its performance is significantly improved, achieving a more efficient use effect.

CN118932743BActive Publication Date: 2024-12-20NANTONG XUEFAN ENG MATERIALS TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411413558.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-20
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing geotextile has poor strength and low acid and alkali resistance and aging resistance, which limits its efficiency.

Method used

The modified glue and the modified coating agent are used to form the glue layer and the spray modified layer respectively. The combined arrangement of the spray modified layer, the glue layer and the geotextile matrix is ​​enhanced to enhance the strength performance and acid and alkali resistance stability of the geotextile. . Modified glue solution includes polyurethane glue, silane coupling agent, modified filler agent and acetone solvent, and modified coating agent includes bisphenol A type epoxy resin, 2-phenylimidazole curing agent, acetone solvent and actolite blending agent . Modified filler and actolite blender improve material properties through specific preparation methods.

Benefits of technology

It significantly improves the strength performance of geotextiles, acid and alkali resistance, aging resistance stability, and improves the efficiency of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an acid- and alkali-resistant geotextile and a preparation method thereof, wherein the acid- and alkali-resistant geotextile comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom. In the preparation process of the acid- and alkali-resistant geotextile of the invention, a modified adhesive is used to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer. The adhesive layer and the spray-modified layer are coordinated and enhanced together, so that the obtained product has excellent geotextile strength performance, and the acid- and alkali-resistant and aging-resistant stability effects of the product are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geotextiles, and in particular to an acid- and alkali-resistant geotextile and a preparation method thereof. Background Art

[0002] Geotextile, also known as geotextile, is a water-permeable geosynthetic material made of synthetic fibers through needle punching or weaving. Geotextile is one of the new geosynthetics. The finished product is in the shape of cloth, generally 4-6 meters wide and 50-100 meters long. Geotextile is divided into woven geotextile and non-woven filament geotextile.

[0003] The existing geotextiles have poor strength performance, and the acid and alkali resistance and aging resistance of the products are poor, which limits the use efficiency of the products. Based on this, the present invention further improves and processes them. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide an acid- and alkali-resistant geotextile and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides an acid- and alkali-resistant geotextile, comprising a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0007] The modified rubber solution comprises the following raw materials in parts by weight:

[0008] 20-30 parts of polyurethane glue, 2-5 parts of silane coupling agent KH560, 2-4 parts of modified filler and 10-15 parts of acetone solvent;

[0009] The modified coating comprises the following raw materials in parts by weight:

[0010] 10-15 parts of bisphenol A epoxy resin, 2-5 parts of 2-phenylimidazole curing agent, 4-7 parts of acetone solvent and 3-6 parts of rectorite conditioning agent.

[0011] Preferably, the preparation method of the modified filler is:

[0012] S1: 3-5 parts of wollastonite, 1-3 parts of nano silica sol, 2-4 parts of dopamine hydrochloride solution and 3-5 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after the stirring is completed, the mixture is washed with water and dried to obtain a wollastonite agent;

[0013] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, blend 4-7 parts of dry flaky talc, 2-5 parts of wollastonite and 2-5 parts of yttrium nitrate solution and ball mill at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water and dry to obtain a modified filler.

[0014] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%.

[0015] Preferably, the mixing and stirring process is carried out at a stirring speed of 450-550 r / min and the stirring time is 20-30 min.

[0016] Preferably, the mass fraction of the yttrium nitrate solution is 3-5%.

[0017] Preferably, the stirring speed is 500 r / min, and the stirring time is 25 min.

[0018] Preferably, the preparation method of the rectorite conditioning agent is:

[0019] S11: heat treating the rectorite at 150-170°C for 5-10 min, then cooling to 55°C at a rate of 2-5°C / min, and keeping the temperature;

[0020] S12: 4-7 parts of heat-insulated rectorite, 2-3 parts of sodium citrate solution, 3-5 parts of lanthanum chloride solution and 2-5 parts of bentonite are mixed and ball-milled at a ball-milling speed of 1500-1700 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0021] Preferably, the mass fraction of the sodium citrate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.

[0022] Preferably, the bentonite is further soaked in a sodium silicate solution having a mass fraction of 5% at a temperature of 55-60° C. for 2 hours, and then filtered and dried after the soaking is completed.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The acid and alkali resistant geotextile of the present invention adopts modified glue to form a glue layer, and finally sprays a modified coating to form a spray modified layer. The glue layer and the spray modified layer are coordinated and synergistically enhanced, so that the obtained product has excellent geotextile strength performance, and the acid and alkali resistance and aging resistance of the product are remarkable. DETAILED DESCRIPTION

[0025] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The acid- and alkali-resistant geotextile of the present embodiment comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0027] The modified rubber solution comprises the following raw materials in parts by weight:

[0028] 20-30 parts of polyurethane glue, 2-5 parts of silane coupling agent KH560, 2-4 parts of modified filler and 10-15 parts of acetone solvent;

[0029] The modified coating comprises the following raw materials in parts by weight:

[0030] 10-15 parts of bisphenol A epoxy resin, 2-5 parts of 2-phenylimidazole curing agent, 4-7 parts of acetone solvent and 3-6 parts of rectorite conditioning agent.

[0031] The preparation method of the modified filler of this embodiment is:

[0032] S1: 3-5 parts of wollastonite, 1-3 parts of nano silica sol, 2-4 parts of dopamine hydrochloride solution and 3-5 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after the stirring is completed, the mixture is washed with water and dried to obtain a wollastonite agent;

[0033] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, blend 4-7 parts of dry flaky talc, 2-5 parts of wollastonite and 2-5 parts of yttrium nitrate solution and ball mill at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water and dry to obtain a modified filler.

[0034] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%.

[0035] The stirring speed of the blending and stirring process in this embodiment is 450-550r / min, and the stirring is 20-30min.

[0036] The mass fraction of the yttrium nitrate solution in this embodiment is 3-5%.

[0037] The stirring speed of this embodiment is 500r / min, and the stirring is 25min.

[0038] The preparation method of the rectorite blending agent of the present embodiment is:

[0039] S11: heat treating the rectorite at 150-170°C for 5-10 min, then cooling to 55°C at a rate of 2-5°C / min, and keeping the temperature;

[0040] S12: 4-7 parts of heat-insulated rectorite, 2-3 parts of sodium citrate solution, 3-5 parts of lanthanum chloride solution and 2-5 parts of bentonite are mixed and ball-milled at a ball-milling speed of 1500-1700 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0041] The mass fraction of the sodium citrate solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%

[0042] The bentonite of this embodiment is also treated by soaking in a sodium silicate solution with a mass fraction of 5% at a temperature of 55-60° C. for 2 hours. After the soaking is completed, the solution is filtered and dried.

[0043] Example 1.

[0044] The acid- and alkali-resistant geotextile of the present embodiment comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0045] The modified rubber solution comprises the following raw materials in parts by weight:

[0046] 20 parts of polyurethane glue, 2 parts of silane coupling agent KH560, 2 parts of modified filler and 10 parts of acetone solvent;

[0047] The modified coating comprises the following raw materials in parts by weight:

[0048] 10 parts of bisphenol A epoxy resin, 2 parts of 2-phenylimidazole curing agent, 4 parts of acetone solvent and 3 parts of rectorite conditioning agent.

[0049] The preparation method of the modified filler of this embodiment is:

[0050] S1: 3 parts of wollastonite, 1 part of nano silica sol, 2 parts of dopamine hydrochloride solution and 3 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after the stirring is completed, the mixture is washed with water and dried to obtain a wollastonite agent;

[0051] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution, stir and mix, then wash with water and dry, blend 4 parts of dry flaky talc, 2 parts of wollastonite and 2 parts of yttrium nitrate solution and ball mill at a ball milling speed of 1000 r / min for 1 hour. After the ball milling is completed, wash with water and dry to obtain a modified filler.

[0052] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%.

[0053] The stirring speed of the blending and stirring process in this embodiment is 450r / min, and the stirring is performed for 20min.

[0054] The mass fraction of the yttrium nitrate solution in this embodiment is 3%.

[0055] The preparation method of the rectorite blending agent of the present embodiment is:

[0056] S11: heat treating the rectorite at 150°C for 5 min, then cooling to 55°C at a rate of 2°C / min, and keeping the temperature;

[0057] S12: 4 parts of heat-insulated rectorite, 2 parts of sodium citrate solution, 3 parts of lanthanum chloride solution and 2 parts of bentonite are mixed and ball-milled at a speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0058] The mass fraction of the sodium citrate solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 4%

[0059] The bentonite of this embodiment is also treated by soaking in a sodium silicate solution with a mass fraction of 5% at a temperature of 55° C. for 2 hours. After the soaking is completed, the solution is filtered and dried.

[0060] Example 2.

[0061] The acid- and alkali-resistant geotextile of the present embodiment comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0062] The modified rubber solution comprises the following raw materials in parts by weight:

[0063] 30 parts of polyurethane glue, 5 parts of silane coupling agent KH560, 4 parts of modified filler and 15 parts of acetone solvent;

[0064] The modified coating comprises the following raw materials in parts by weight:

[0065] 15 parts of bisphenol A epoxy resin, 5 parts of 2-phenylimidazole curing agent, 7 parts of acetone solvent and 6 parts of rectorite conditioning agent.

[0066] The preparation method of the modified filler of this embodiment is:

[0067] S1: 5 parts of wollastonite, 3 parts of nano silica sol, 4 parts of dopamine hydrochloride solution and 5 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after the stirring is completed, the mixture is washed with water and dried to obtain a wollastonite agent;

[0068] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, blend 7 parts of dry flaky talc, 5 parts of wollastonite and 5 parts of yttrium nitrate solution and ball mill at a speed of 1500 r / min for 1 hour, wash with water and dry to obtain a modified filler.

[0069] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%.

[0070] The stirring speed of the blending and stirring process in this embodiment is 550r / min, and the stirring is 30min.

[0071] The mass fraction of the yttrium nitrate solution in this embodiment is 5%.

[0072] The preparation method of the rectorite blending agent of the present embodiment is:

[0073] S11: heat treating the rectorite at 170°C for 10 min, then cooling to 55°C at a rate of 5°C / min, and keeping the temperature;

[0074] S12: 7 parts of heat-insulated rectorite, 3 parts of sodium citrate solution, 5 parts of lanthanum chloride solution and 5 parts of bentonite are mixed and ball-milled at a ball-milling speed of 1700 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0075] The mass fraction of the sodium citrate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 7%

[0076] The bentonite of this embodiment is also treated by soaking in a sodium silicate solution with a mass fraction of 5% at a temperature of 60° C. for 2 hours. After the soaking is completed, the solution is filtered and dried.

[0077] Example 3.

[0078] The acid- and alkali-resistant geotextile of the present embodiment comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0079] The modified rubber solution comprises the following raw materials in parts by weight:

[0080] 25 parts of polyurethane glue, 3.5 parts of silane coupling agent KH560, 3 parts of modified filler and 12.5 parts of acetone solvent;

[0081] The modified coating comprises the following raw materials in parts by weight:

[0082] 12.5 parts of bisphenol A epoxy resin, 3.5 parts of 2-phenylimidazole curing agent, 5.5 parts of acetone solvent and 4.5 parts of rectorite conditioning agent.

[0083] The preparation method of the modified filler of this embodiment is:

[0084] S1: 4 parts of wollastonite, 2 parts of nano-silica sol, 3 parts of dopamine hydrochloride solution and 4 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after stirring, the mixture is washed with water and dried to obtain a wollastonite agent;

[0085] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, blend 5.5 parts of dry flaky talc, 3.5 parts of wollastonite and 3.5 parts of yttrium nitrate solution and ball mill at a ball mill speed of 1250 r / min for 1 hour. After the ball milling is completed, wash with water and dry to obtain a modified filler.

[0086] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%.

[0087] The mixing speed of the blending and stirring process in this embodiment is 500 r / min, and the stirring is for 5 minutes.

[0088] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.

[0089] The preparation method of the rectorite blending agent of the present embodiment is:

[0090] S11: heat treating the rectorite at 160°C for 7.5 min, then cooling to 55°C at a rate of 3.5°C / min, and keeping the temperature;

[0091] S12: 5.5 parts of heat-insulated rectorite, 2.5 parts of sodium citrate solution, 4 parts of lanthanum chloride solution and 3.5 parts of bentonite are mixed and ball-milled at a speed of 1600 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0092] The mass fraction of the sodium citrate solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 5%

[0093] The bentonite of this embodiment is also treated by soaking in a sodium silicate solution with a mass fraction of 5% at a temperature of 57° C. for 2 hours. After the soaking is completed, the solution is filtered and dried.

[0094] Example 4.

[0095] The acid- and alkali-resistant geotextile of the present embodiment comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0096] The modified rubber solution comprises the following raw materials in parts by weight:

[0097] 22 parts of polyurethane glue, 3 parts of silane coupling agent KH560, 3 parts of modified filler and 12 parts of acetone solvent;

[0098] The modified coating comprises the following raw materials in parts by weight:

[0099] 12 parts of bisphenol A epoxy resin, 3 parts of 2-phenylimidazole curing agent, 5 parts of acetone solvent and 3-6 parts of rectorite conditioning agent.

[0100] The preparation method of the modified filler of this embodiment is:

[0101] S1: 5 parts of wollastonite, 2 parts of nano silica sol, 3 parts of dopamine hydrochloride solution and 4 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after the stirring is completed, the mixture is washed with water and dried to obtain a wollastonite agent;

[0102] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, blend 5 parts of dry flaky talc, 3 parts of wollastonite and 3 parts of yttrium nitrate solution and ball mill at a speed of 1200 r / min for 1 hour, wash with water and dry to obtain a modified filler.

[0103] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3%.

[0104] The stirring speed of the blending and stirring process in this embodiment is 460r / min, and the stirring time is 22min.

[0105] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.

[0106] The preparation method of the rectorite blending agent of the present embodiment is:

[0107] S11: heat treating the rectorite at 155°C for 6 min, then cooling to 55°C at a rate of 3°C / min, and keeping the temperature;

[0108] S12: 5 parts of heat-insulated rectorite, 2 parts of sodium citrate solution, 4 parts of lanthanum chloride solution and 3 parts of bentonite are mixed and ball-milled at a ball-milling speed of 1550 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0109] The mass fraction of the sodium citrate solution in this embodiment is 3%; the mass fraction of the lanthanum chloride solution is 5%

[0110] The bentonite of this embodiment is also treated by soaking in a sodium silicate solution with a mass fraction of 5% at a temperature of 56° C. for 2 hours. After the soaking is completed, the solution is filtered and dried.

[0111] Example 5.

[0112] The acid- and alkali-resistant geotextile of the present embodiment comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0113] The modified rubber solution comprises the following raw materials in parts by weight:

[0114] 28 parts of polyurethane glue, 4 parts of silane coupling agent KH560, 3 parts of modified filler and 14 parts of acetone solvent;

[0115] The modified coating comprises the following raw materials in parts by weight:

[0116] 14 parts of bisphenol A epoxy resin, 4 parts of 2-phenylimidazole curing agent, 6 parts of acetone solvent and 3-6 parts of rectorite conditioning agent.

[0117] The preparation method of the modified filler of this embodiment is:

[0118] S1: 4 parts of wollastonite, 2 parts of nano-silica sol, 3 parts of dopamine hydrochloride solution and 4 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after stirring, the mixture is washed with water and dried to obtain a wollastonite agent;

[0119] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, blend 6 parts of dry flaky talc, 4 parts of wollastonite and 4 parts of yttrium nitrate solution and ball mill at a ball milling speed of 1450 r / min for 1 hour, wash with water and dry to obtain a modified filler.

[0120] The mass fraction of the dopamine hydrochloride solution in this embodiment is 4%.

[0121] The stirring speed of the blending and stirring process in this embodiment is 520r / min, and the stirring time is 28min.

[0122] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.

[0123] The preparation method of the rectorite blending agent of the present embodiment is:

[0124] S11: heat treating the rectorite at 16°C for 8 min, then cooling to 55°C at a rate of 4°C / min, and keeping the temperature;

[0125] S12: 6 parts of heat-insulated rectorite, 3 parts of sodium citrate solution, 4 parts of lanthanum chloride solution and 4 parts of bentonite are mixed and ball-milled at a speed of 1600 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0126] The mass fraction of the sodium citrate solution in this embodiment is 4%; the mass fraction of the lanthanum chloride solution is 6%

[0127] The bentonite of this embodiment is also treated by soaking in a sodium silicate solution with a mass fraction of 5% at a temperature of 58° C. for 2 hours. After the soaking is completed, the solution is filtered and dried.

[0128] Example 6.

[0129] The acid- and alkali-resistant geotextile of the present embodiment comprises a geotextile substrate, the geotextile substrate is immersed in a modified adhesive to form an adhesive layer, and finally a modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom;

[0130] The modified rubber solution comprises the following raw materials in parts by weight:

[0131] 22 parts of polyurethane glue, 4 parts of silane coupling agent KH560, 3 parts of modified filler and 12 parts of acetone solvent;

[0132] The modified coating comprises the following raw materials in parts by weight:

[0133] 14 parts of bisphenol A epoxy resin, 3 parts of 2-phenylimidazole curing agent, 5 parts of acetone solvent and 3-6 parts of rectorite conditioning agent.

[0134] The preparation method of the modified filler of this embodiment is:

[0135] S1: 4 parts of wollastonite, 2 parts of nano-silica sol, 3 parts of dopamine hydrochloride solution and 4 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after stirring, the mixture is washed with water and dried to obtain a wollastonite agent;

[0136] S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, blend 5 parts of dry flaky talc, 4 parts of wollastonite and 3 parts of yttrium nitrate solution and ball mill at a ball milling speed of 1200 r / min for 1 hour, wash with water and dry to obtain a modified filler.

[0137] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3%.

[0138] The stirring speed of the blending and stirring process in this embodiment is 530 r / min, and the stirring time is 28 min.

[0139] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.

[0140] The preparation method of the rectorite blending agent of the present embodiment is:

[0141] S11: heat treating the rectorite at 165°C for 8 min, then cooling to 55°C at a rate of 4°C / min, and keeping the temperature;

[0142] S12: 6 parts of heat-insulated rectorite, 3 parts of sodium citrate solution, 4 parts of lanthanum chloride solution and 4 parts of bentonite are mixed and ball-milled at a ball-milling speed of 1650 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent.

[0143] The mass fraction of the sodium citrate solution in this embodiment is 4%; the mass fraction of the lanthanum chloride solution is 6%

[0144] The bentonite of this embodiment is also treated by soaking in a sodium silicate solution with a mass fraction of 5% at a temperature of 57° C. for 2 hours. After the soaking is completed, the solution is filtered and dried.

[0145] Comparative Example 1.

[0146] The difference from Example 3 is that no modified filler is added.

[0147] Comparative Example 2.

[0148] The difference from Example 3 is that no wollastonite agent is added to the modified filler.

[0149] Comparative Example 3.

[0150] The difference from Example 3 is that the wollastonite agent is replaced by wollastonite.

[0151] Comparative Example 4.

[0152] The difference from Example 3 is that no dry flaky talc is added to the modified filler.

[0153] Comparative Example 5.

[0154] The difference from Example 3 is that no rectorite conditioning agent is added.

[0155] Comparative Example 6.

[0156] The difference from Example 3 is that no heat-insulating rectorite is added to the rectorite blending agent.

[0157] Comparative Example 7.

[0158] The difference from Example 3 is that no heat-insulating rectorite is added to the rectorite conditioning agent.

[0159] The performance of the products of Examples 1-6 and Comparative Examples 1-7 was tested under normal conditions, and the products were treated in 2% hydrochloric acid for 24 hours and 2% sodium hydroxide mist for 24 hours to test the acid and alkali resistance of the products. , the product aging resistance was tested under weathering and aging conditions of 20ppm ozone concentration and 35℃ for 24h. The test is as follows:

[0160]

[0161] It can be seen from Comparative Examples 1-7 and Example 3 that the product of Example 3 has excellent tensile strength performance, and the acid and alkali resistance and anti-aging stability of the product are remarkable;

[0162] The performance of the product is significantly deteriorated when one of the modified filler and the rectorite conditioning agent is added and not added. At the same time, the performance of the product also shows a relatively obvious deterioration trend when the wollastonite agent is not added to the modified filler. The performance of the product also shows a deterioration trend when the dry flaky talcum powder is not added to the modified filler, the heat-insulating rectorite is not added to the rectorite conditioning agent, and the heat-insulating rectorite is not added to the rectorite conditioning agent. The performance of the product all shows a deterioration trend. The modified filler and the rectorite conditioning agent obtained by the specific method of the present invention have the most significant product performance effect, and the effects of other methods are not as obvious as those of the present invention.

[0163] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An acid- and alkali-resistant geotextile, comprising a geotextile substrate, characterized in that: The geotextile substrate is immersed in the modified adhesive to form an adhesive layer, and finally the modified coating is sprayed to form a spray-modified layer, wherein the spray-modified layer, the adhesive layer and the geotextile substrate are arranged in sequence from top to bottom; The modified rubber solution comprises the following raw materials in parts by weight: 20-30 parts of polyurethane glue, 2-5 parts of silane coupling agent KH560, 2-4 parts of modified filler and 10-15 parts of acetone solvent; The modified coating comprises the following raw materials in parts by weight: 10-15 parts of bisphenol A epoxy resin, 2-5 parts of 2-phenylimidazole curing agent, 4-7 parts of acetone solvent and 3-6 parts of rectorite conditioning agent; The preparation method of the modified filler is: S1: 3-5 parts of wollastonite, 1-3 parts of nano-silica sol, 2-4 parts of dopamine hydrochloride solution and 3-5 parts of sodium dodecylbenzene sulfonate are mixed and stirred, and after the stirring is completed, the mixture is washed with water and dried to obtain a wollastonite agent; S2: Place flaky talc in a sufficient amount of 5% by mass potassium permanganate solution and stir to mix, then wash with water and dry, mix 4-7 parts of dried flaky talc, 2-5 parts of wollastonite and 2-5 parts of yttrium nitrate solution and ball mill at a ball milling speed of 1000-1500 r / min for 1 hour, wash with water and dry to obtain a modified filler; The preparation method of the rectorite conditioning agent is: S11: heat treating the rectorite at 150-170°C for 5-10 min, then cooling to 55°C at a rate of 2-5°C / min, and keeping the temperature; S12: 4-7 parts of heat-insulated rectorite, 2-3 parts of sodium citrate solution, 3-5 parts of lanthanum chloride solution and 2-5 parts of bentonite are mixed and ball-milled at a ball-milling speed of 1500-1700 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a rectorite blending agent, wherein the mass fraction of the sodium citrate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.

2. The acid- and alkali-resistant geotextile according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%.

3. The acid- and alkali-resistant geotextile according to claim 1, characterized in that: The mixing speed of the blending and stirring process in S1 is 450-550 r / min, and the stirring is performed for 20-30 min.

4. The acid- and alkali-resistant geotextile according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 3-5%.

5. The acid- and alkali-resistant geotextile according to claim 1, characterized in that: The stirring speed in S2 is 500 r / min, and the stirring is carried out for 25 min.

6. The acid- and alkali-resistant geotextile according to claim 1, characterized in that: The bentonite is also soaked in a sodium silicate solution with a mass fraction of 5% at a temperature of 55-60° C. for 2 hours. After the soaking is completed, the bentonite is filtered and dried.

Citation Information

Patent Citations

  • Special epoxy powder coating for thick-coated steel strand

    CN106752722A

  • High-strength carbon-fiber compound fabric

    CN109624429A

  • High-elasticity honeycomb structure TPU (thermoplastic polyurethane) high-low temperature film and forming process thereof

    CN118003742A

  • Wear-resistant scratch-resistant shading ABS (acrylonitrile-butadiene-styrene) material and preparation method thereof

    CN118325276A

  • High-weather-resistance and high-corrosion-resistance powder coating for energy storage equipment and preparation method of high-weather-resistance and high-corrosion-resistance powder coating

    CN118546587A